Impact of air-plasma treatment at atmospheric pressure on wood and wood extractives. (2nd April 2016) - Avramidis, G.; Wascher, R.; Militz, H.; Viöl, W.
Abstract : This study addresses the question of whether the extractives or the main components of wood are responsible for the alterations in surface energy after air-plasma treatment. For this purpose, x-ray photoelectron spectroscopy was carried out on untreated, microtomed and air-plasma-modified beech wood surfaces. A dielectric barrier discharge at atmospheric pressure was used for plasma modification. The results indicate that air-plasma treatment affects the O/C-ratio and surface energy characteristics of wood surfaces by oxidative alteration and exposition of the wood main components.